Offense-Supportive Cognitions Expressed by Men Who Use Internet to Sexually Exploit Children: A Thematic Analysis - Paquette, Sarah (International journal of offender therapy and comparative criminology, 2022)
Although offense-supportive cognitions are related to the maintenance of contact sexual offending behavior, it is unknown whether this finding also applies to online sexual offending behavior. A few studies have examined the cognitions of men convicted for using child sexual exploitation material, but findings remain limited due to important methodological limitations. Furthermore, fewer studies have investigated the cognitions of men who use the internet to solicit sexual activities with children. The objective of this study was to examine the nature of the cognitions that support online sexual offending against children. The content of police interviews was analyzed using a thematic analysis to identify the cognitive themes present in the offense-related views expressed by 20 men who consumed child sexual exploitation material, 15 who sexually solicited children, and 18 who committed both types of online offenses. Results revealed eight cognitive themes that reflected four underlying themes related to interpersonal relationships, the sexualisation of children, perceptions of the self, and perceptions of the virtual environment. Findings indicate that while the cognitive themes of the three groups are similar, their specific content varies according to the types of offenses. Implications for future research are discussed.